Дослідження в Острозі по вул. Академічна, 12 - Прищепа, Б.А.; Бондарчук, О.А.; Позіховський, О.Л. (Археологічні дослідження в Україні, 2010)
Results of the research conducted at 12, Akademichna Street in Ostroh in 2008 are presented. On the plot allotted for the construction of a church, cultural layers and objects of Late Trypillya culture, the Slavic and the Ancient Rus periods, Lithuanian and Polish epoch, and graves from the 16th c. to the 18th c. were studied.